N-ACETYL-S-(N-METHYLCARBAMOYL)-CYSTEINE (AMCC) as Cumulative Biomonitoring of Dimethylformamide Exposure among Industrial Workers - Arifianto, Angga; Ilyas, Muhammad; ., Herqutanto (Occupational and Environmental Medicine Journal of Indonesia, 2024)
Background: N,N-Dimethylformamide (DMF) is an aliphatic amide which is miscible with water and a majority of organic liquids. Due to its amphiphilic properties, it is a widely used industrial solvent, especially for polymers. DMF has been consistently hepatotoxic, inducing effects on the liver at lowest concentrations or doses. N-acetyl-S-(N-methylcarbamoyl)cysteine (AMCC) which is one major metabolites of DMF, found in urine after DMF exposure of the whole workweek. Objective: To determine the way of AMCC can be use as biomarker of DMF exposure and the best possible sampling time. Method: This study conducted a literature search using evidence-based databases focusing on clinical questions using the “PICO” method. The author searched the relevant articles using the following databases: “PubMed”, “Scopus”, and “Embase”. The keywords used included “Dimethylformamide”, “Workes,” “AMCC” (MESH Term), “N-Acetyl-S-(N-Methylcarbamoyl)cysteine,” along with their synonyms combined with Boolean operators. Inclusion criteria comprised studies involving workers populations, cohort, cross sectional, systematic reviews/meta-analyses, written in English, and with full-text availability. Exclusion criteria included case report, RCT, and articles with incomplete data or inaccessible full text. Results: Based on the analysis of five reviewed literature, the author obtained insights into the effectiveness of AMCC use as biomarker of DMF exposure. It can be use after several workdays exposure of DMF (3-5 days). The best of time sampling is at morning or afternoon of last day on the workweek. AMCC result is described as cumulative DMF exposure of a whole week, and more relevant associated with the hepatotoxicity of DMF than the other DMF metabolite, N-methylformamide (NMF). Conclusion: AMCC can be considered as a cumulative exposure of DMF of a whole week and more relevant associated with DMF induced hepatotoxicity. Keywords: Dimethylformamide, Worker, AMCC